Regional variations and trends in the composition and vulnerability of rural livelihoods - Belton, Ben; Filipski, Mateusz J.; Lambrecht, Isabel B.; Fang, Peixun (International Food Policy Research Institute, 2023)
The regional context in which rural livelihoods in Myanmar are embedded varies widely, in terms of physical geography, climate and agroecology, local resource base, agrarian structure, infrastructure provision, proximity to urban areas and neighboring countries, social networks, institutions, and ethnicities. The composition of livelihoods in each administrative and geographical zone of the country reflects these diverse contexts. Marked variations in patterns of livelihoods are evident at multiple scales, from the zone or region, down to township, and village level, so that the composition of livelihoods in villages close to one another sometimes varies widely (Phyo, 2022). Despite a high level of place-based specificity, many broad similarities and common trends also shape the composition of livelihoods at sub-national and national levels. These include: Generally low levels of agricultural productivity relative to other countries in the region, in terms of both land and labor (World Bank 2016); High rates of landlessness and legacies of land confiscation and unresolved struggles over land rights and access (Mark and Belton 2020); Generally poor, though -prior to 2020 - rapidly improving, public infrastructure and services, including electricity, roads, schools, health services, and rural credit (Belton et al. 2017; Lambrecht and Belton 2018); Relatively low levels of diversification and capital in the rural non-farm economy; High rates of international and domestic outmigration (World Bank and LIFT 2016; CHIME 2019); Histories of ethno-political conflict and insecurity (South 2009). This working paper synthesizes analyses from four large household surveys, each covering a major agro-ecological zone, to evaluate inter-regional variations in the composition of livelihoods and the rural economy. The four zones examined are the Delta (Ayeyarwady and Yangon), the Dry Zone (Mandalay, Magway, Sagaing), the hills (represented by Shan South), and the coasts (represented by Mon State). We also synthesize recent secondary sources that offer additional context and insights on regional livelihood dynamics from these and other areas of Myanmar, including the impacts of the ‘triple crisis’ (covid, coup, and price inflation) beginning in 2020.